Research Commentary—Reframing the Dominant Quests of Information Systems Strategy Research for Complex Adaptive Business Systems - Tanriverdi, Hüseyin; Rai, Arun; Venkatraman, N. (Information Systems Research, 2010)
We review and reframe three main quests of research on information systems (IS) strategy: (1) the strategic alignment quest, (2) the integration quest, and (3) the sustained competitive advantage quest. The assumptions and logic of these quests have become less relevant in increasingly complex adaptive business systems (CABS), where the competitive performance landscapes of products and services are highly dynamic and co-evolve. We revise the strategic alignment quest to propose a co-evolution quest that addresses not only competitive strategy questions of a firm but also corporate strategy questions. The co-evolution quest seeks to increase a firm's agility and dynamism in repositioning itself, identifying profitable product-market positions as the evolving competitive landscape erodes the profitability of the firm's existing positions. To support the co-evolution quest, we revise the integration quest and propose a reconfiguration quest that encompasses not only business processes but also products and services, as well as the contracts, resources, and transactions associated with them. As the firm makes repositioning moves to co-evolve with the competitive landscape, the reconfiguration quest seeks to increase the firm's agility in disintegrating its existing nexus of contracts, resources, and transactions that support the old positions and in reconfiguring new ones that support the new positions. Finally, we revise the sustained competitive advantage quest to propose a renewal quest that recognizes the temporary nature of competitive advantage in CABS. The renewal quest seeks to destabilize the firm's old sources of competitive advantage when competitive dynamics erode their utility, rapidly create new sources of competitive advantage, and concatenate a series of temporary advantages over time. The three reframed quests provide the foundation for a research agenda on IS strategy in CABS.